A Detailed Review on Diabetic Wound Healing Activity - Bhopale, Raman S.; Jangam, Rajesh D.; Dhekale, Harshada M.; Aiwale, Prachi P.; Chaware, Vitthal J.; K. Redasani, Vivekkumar (Asian Journal of Pharmaceutical Research and Development, 2023)
Skin damage is known as a wound. Hemostasis, inflammatory, proliferative, and tissue remodelling or resolution are the four perfectly timed and highly planned phases that make up the normal biological process of wound healing in the human body. There are two basic categories of wounds: acute wounds and chronic wounds. Long-term negative effects on one’s health are caused by the chronic metabolic condition known as diabetes mellitus, which is becoming more common. 25 percent of those with diabetes mellitus are thought to have poor wound healing due to their diabetes. Oxygenation, infection, hormones related to ageing and sex, stress, diabetes, and obesity, drugs, alcoholism, smoking, and diet are among the factors that affect wound healing. To address their basic medical needs, According to estimates, 80% of people who live in underdeveloped nations need traditional medicines, which are typically made from medicinal plants. Numerous individuals in Africa and other poor nations employ using medicinal herbs to cure diabetic wounds and associated issues due to the abundant supply With therapeutic herbs and enough conventional wisdom regarding wounds healing. Recent developments in functional genomics, nanotechnology, wound healing in diabetics, along with a better knowing the pathophysiology of chronic wounds. In the following review, detailed information about healing of diabetic wounds with mechanism, factors affecting, impairment of wound healing with its pathophysiology, herbal treatments and current advances when treating diabetic wounds are examined.